Demographic profile, prevalence, pattern, and risk factors for retinal vein occlusion in Liberia: A retrospective study - Singh, Gurcharan; Pillai, Shayri (Oman journal of ophthalmology, 2024)
PURPOSE: This study aims to describe the demographic profile, prevalence, pattern, and risk factors for retinal vein occlusion (RVO) in patients over 40 years of age presenting to the Liberia Eye Centre, John F Kennedy Memorial Medical Centre, Monrovia, Liberia. SUBJECTS AND METHODS: A retrospective study was conducted on patients presenting to Liberia Eye Centre from July 2017 to February 2021. A total of 17506 new patients were examined during this period out of which 10813 patients were over 40 years of age. Data were collected from the electronic medical record system database. The variables in the collected data included age, gender, location, laterality of eye affected, uncorrected visual acuity, best-corrected visual acuity, intraocular pressure, ocular diagnosis, systemic risk factors, and associated complications. RESULTS: Of the 10813 patients, RVO was found in 111 patients with an overall prevalence rate of 1.03% (95% confidence interval 0.80-1.2). Central RVO (CRVO) was more common than branch RVO (BRVO) in the defined population with similar proportions of both genders. The mean age for any RVO was 64.45 ± 12.27 standard deviation (SD) years (P = 0.734). Majority of the cases of RVO were from Lofa (n = 20; 18%). Fifty-five (61.1%) patients had hypertension, 5 (5.6%) had diabetes mellitus, and 6 (6.7%) had dyslipidemia. More than one systemic risk factor was present in 24 (26.7%) patients. However, none of the systemic risk factors were statistically significant. Visual acuity was most affected in patients with CRVO, with a visual acuity of <3/60 in 45 (63.4%) patients compared to 12 (30.0%) in BRVO patients. Glaucoma was present in 34 (30.6%) patients. The most common ocular complication was macular edema (n = 62, 55.8%) followed by vitreous hemorrhage (n = 8, 7.2%). CONCLUSIONS: RVO was detected in 1.03% of the study population over the age of 40 years in Liberia, CRVO being more common than BRVO. The clinical presentation of RVO in the Liberian population for the first time provides insight into the burden of the disease and opportunity for further research.